CHARACTERISTICS OF 'PARKAN HUMOR' IN WAYANG WONG'S PERFORMANCE - Indah Zulhidayati (Universitas Negeri Makassar, 2023)
Parkan as the life of the Wayang Wong show in Sembalun, his presence is always awaited by the audience. Parkan's regeneration is important for the survival of Wong puppet art in Sembalun Bumbung. The purpose of this study was to find out the characteristics of the cast masks and the characteristics of Parkan's humor. This stage of research uses qualitative research with a cultural studies approach. The location of this study is in Sembalun Bumbung, East Lombok in the Wayang Wong art group. The data collection technique used by researchers is by means of observation, interviews, and analysis of secondary data (text, photo, video of Wayang Wong performance). Meanwhile, the data analysis techniques used are data reduction, data presentation, and data verification. The result of this study is that there are two characteristics of Parkan humor, namely planned and improvised. In planned humor, there are six concepts of humor presented, namely Pecangklitan Humor, Mewaran, Komikan, Syair, and Penter Blok.